Plasma polyacrylic acid and hollow TiO2 spheres modified with rhodamine B for sensitive electrochemical sensing Cu(ii). (30th November 2015) - Zhang, Zhihong; Ji, Hongfei; Zhang, Shuai; Peng, Donglai; Fu, Qixuan; Wang, Minghua; He, Linghao; Yue, Lingyu
Abstract : A rhodamine B-modified nanocomposite-based electrochemical sensor was fabricated for selectively and sensitively detecting Cu(ii ) in environmental fields. Abstract : We report a novel nanocomposite of hollow TiO2 microspheres and plasma polyacrylic acid (TiO2 @PPAA) modified with rhodamine B (TiO2 @PPAA-RhB). This nanocomposite was further used as an electrochemical sensor for the ultra-sensitive and selective detection of Cu 2+ in water. A gold electrode was modified with hollow TiO2 nanospheres, followed by the closely bonded layer of PPAA via plasma polymerization. Subsequently, the carboxyl groups of TiO2 @PPAA nanocomposites were activated to ester groups by N -hydroxysuccinimide/1-ethyl-3-(3-dimethylaminoprolyl) carbodiimide hydrochloride. The resultant activated ester groups reacted with the amino groups on rhodamine to form the amide groups, leading to the modification of TiO2 @PPAA nanocomposites with rhodamine. Considering the synergistic effect of strong electrostatic interaction between the carboxyl groups of PPAA and Cu 2+, the direct adsorption of Cu 2+ on the TiO2 surface, and the coordination chemistry formed between Cu 2+ and rhodamine, the developed electrochemical biosensor exhibited high sensitivity of Cu 2+ detection, with a detection limit of 0.404 pM within the range of 0.001–10 nM of Cu 2+ . Therefore, the fabricated electrochemical sensor based on TiO2 @PPAA-RhB can be obtained via plasma polymerization and represents a highly promising tool for use in environmental monitoring.